2019
DOI: 10.1590/1806-3713/e20170395
|View full text |Cite
|
Sign up to set email alerts
|

Lipoabdominoplasty: repercussions for diaphragmatic mobility and lung function in healthy women

Abstract: Objective: To evaluate the impact of lipoabdominoplasty on diaphragmatic mobility (DM) and lung function in healthy women. Methods: This was a prospective cohort study using high-resolution ultrasound and forced spirometry to assess DM and lung function, respectively, prior to lipoabdominoplasty, as well as on postoperative day (POD) 10 and POD 30. DM was measured under two conditions: during tidal volume breathing and during a VC maneuver. Results: The sample consisted of 20 women, with a mean age of 39.85 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Abdominoplasty is generally considered a low-risk surgery, and the most common complications reported after abdominoplasty are hematoma (1.4–5.8%), wound infection (1.1–9.9%), and venous thromboembolism (0.06–1.0%) [ 2 ]. Although abdominoplasty has been reported to increase intraabdominal pressure and reduce pulmonary function, it has been considered a transient, self-resolving and subclinical phenomenon [ [3] , [4] , [5] ]. To our knowledge, ours is the first report of severe acute ventilatory failure due to reductions in lung volume and respiratory system compliance after abdominoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominoplasty is generally considered a low-risk surgery, and the most common complications reported after abdominoplasty are hematoma (1.4–5.8%), wound infection (1.1–9.9%), and venous thromboembolism (0.06–1.0%) [ 2 ]. Although abdominoplasty has been reported to increase intraabdominal pressure and reduce pulmonary function, it has been considered a transient, self-resolving and subclinical phenomenon [ [3] , [4] , [5] ]. To our knowledge, ours is the first report of severe acute ventilatory failure due to reductions in lung volume and respiratory system compliance after abdominoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Change in thoracoabdominal mechanics ultimately affects diaphragm mobility [ 5 ] for the reasons mentioned above, resulting in significant muscle dysfunction. Lack of improvement with non-invasive or controlled mechanical ventilation in our patient pointed towards intraabdominal changes as the primary cause of decreased mobility rather than postsurgical diaphragmatic paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Fluhr et al 11 further confirms the need for physicians who deal with patients undergoing lipoabdominoplasty to be aware of the detrimental effects that the procedure has on the respiratory muscles, the diaphragm in particular. Physicians should be especially aware of the possibility that these complications will occur in healthy subjects or after surgical procedures that are not strictly linked to respiratory problems, as in the Fluhr et al study, 11 as well as the chance that they will be present at hospital discharge despite appropriate postoperative follow-up. Such awareness should lead physicians to take the appropriate measures to minimize the occurrence of complications related to and reduce the magnitude of surgically induced respiratory muscle dysfunction.…”
mentioning
confidence: 81%
“…Surgically induced diaphragmatic/respiratory muscle dysfunction can result in a number of postoperative pulmonary complications, including atelectasis and pneumonia, which can increase morbidity and mortality considerably. The study conducted by Fluhr et al, 11 published in the current issue of the JBP, shows the negative repercussions that lipoabdominoplasty, a common type of cosmetic surgery, has for the diaphragms (and lungs) of healthy women. They showed that diaphragm mobility, assessed by M-mode ultrasound, was reduced in the first 10 days after surgery, as were lung volumes, and that both were restored to preoperative values after one month.…”
mentioning
confidence: 99%
“…Respiratory complications like bronchospasm, atelectasis, and pneumonia have been described in the postoperative period after abdominoplasty [4]. Mechanical ventilation (MV) is necessary for many surgical procedures to provide gas exchanges during general anesthesia (GA).…”
Section: Introductionmentioning
confidence: 99%